Inducing affective learning biases with cognitive training and prefrontal tDCS: a proof-of-concept study - Overman, MJ; Browning, M; O'Shea, J (Springer, 2020)
Background Cognitive models of mood disorders emphasize a causal role of negative affective biases in depression. Computational work suggests that these biases may stem from a belief that negative events have a higher information content than positive events, resulting in preferential processing of and learning from negative outcomes. Learning biases therefore represent a promising target for therapeutic interventions. In this proof-of-concept study in healthy volunteers, we assessed the malleability of biased reinforcement learning using a novel cognitive training paradigm and concurrent transcranial direct current stimulation (tDCS).